An Analysis on EFL Learners’ Perspectives of Online Learning during Covid-19 Pandemic - Siti Maysuroh; Laila Wati; Astrid Dwimaulani; Nurul Yusri; Siti Zurriyatun Sholihah (Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia, 2022)
The aim of this research is to investigate EFL students’ perspectives on the utilization of online learning during the COVID-19 pandemic. A survey method was applied. This research involves 40 students of the second, fourth, and sixth semesters of the English Study Program of a private University in Hamzanwadi for the academic year 2020-2021 as the participants. To collect the data, a questionnaire was administered via Google Forms. The data collected were then analyzed using a percentage formula. The results of the study indicate that most of the students believe that online learning has not provided a better experience dan results in improving their competencies. However, they agreed that it provides ease in their learning. In addition, based on the result of questionnaires, more than 50% of the students prefer direct-classroom learning to online learning and only resettled with online learning during the COVID-19 pandemic. In a nutshell, despite the COVID-19 pandemic, students still choose direct classroom learning.